Verb Valency Frame Extraction Using Morphological and Syntactic Features of Croatian - Šojat, Krešimir (Array, 2010)
The paper presents an approach to valency frame extraction for Croatian verbs on basis of morphological and syntactic features of wordforms from syntactically annotated sentences. We have used a gold standard sample of approximately 1200 sentences and 30.000 tokens from the Croatian Dependency Treebank and a frame instance extraction algorithm. We extracted 936 verb frame instances for 424 different verbs – consisting of lemmas, morphosyntactic tags and syntactic functions of the encountered wordforms – and manually assigned tectogrammatical functors to their elements. Distributional properties are given in terms of co-occurrences for each of these features. The obtained results will serve for further development of valency frame extraction procedures.